Leucocytozoon caulleryi discovery utilizing indirect-ELISA in East Java, Indonesia as a new approach in detecting leucocytozoonosis - Endang Suprihati; Lucia Tri Suwanti; Poedji Hastutiek; Nunuk Dyah Retno Lastuti; Akira Ito; Naomi Himeno (Open Veterinary Journal)
Background: Leucocytozoonosis, caused by Leucocytozoon caulleryi, is a significant parasitic disease in poultry and can cause substantial economic losses in the broiler chicken industry while the gloden standard of examination is currently absent.